EXPLAINING THE RELATIONSHIP BETWEEN CONSTRUCTIVIST APPROACH AND PHYSICS LEARNING INTEREST - Anggraini, Dini Puji (Yayasan Amanah Nur Aman, 2025)
This ex post facto quantitative research investigates the relationship and significant influence of the Constructivist Approach on the Physics Learning Interest of Grade XI students. The study is motivated by the consistent challenge of increasing student engagement and positive affective outcomes in complex Physics concepts. The population for this research consisted of 60 Grade XI students at SMA Negeri 1 Secanggang. Saturated sampling was employed, resulting in all 60 students becoming the research sample. Data was collected using validated and highly reliable questionnaires and analyzed through descriptive statistics and simple linear regression using SPSS 25.0. The descriptive analysis confirmed that both the implementation of the Constructivist Approach (Mean = 4.4167) and the students’ Physics Learning Interest (Mean = 4.3800) were categorized as very high. The hypothesis test (t-test) revealed a significant and positive influence of the Constructivist Approach on Physics Learning Interest (tcount=5.426, Sig.=0.000<0.05). The Coefficient of Determination (Adjusted R Square) was 0.418, indicating that the Constructivist Approach contributes 41.8% to the variation in student learning interest, with the remainder being explained by other factors. The findings support the notion that active and student-centered learning environments, characterized by project-based activities and reflective thinking, are crucial for fostering positive affective outcomes in Physics education.